2018
DOI: 10.1016/j.compstruct.2018.03.097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyamide-6,6 (PA 66) nonwoven veils on the mechanical performance of carbon fiber/epoxy composites

Abstract: In this study, carbon fiber/epoxy (CF/EP) composites were interleaved with polyamide-6,6 (PA 66) nonwoven veils at two different areal weight densities (17 and 50 gsm) to improve their delamination resistance against Mode-I loading. Mode-I fracture toughness (DCB), tensile, open hole tensile (OHT), flexural, compression, short beam shear (ILSS) and Charpy-impact tests were performed on the reference and PA 66 interleaved composite specimens. The DCB test results showed that the initiation and propagation Mode-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 36 publications
(34 reference statements)
4
69
0
2
Order By: Relevance
“…31 For instance, Beylergil et al. 25 studied the tensile and compressive properties of a carbon/epoxy [0 o ] 4 laminate interleaved with the 17 and 50 gsm nylon 6,6 nonwoven fabrics. They showed that the tensile and compressive strength decreased with improved areal weight density by about 41% and 13%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…31 For instance, Beylergil et al. 25 studied the tensile and compressive properties of a carbon/epoxy [0 o ] 4 laminate interleaved with the 17 and 50 gsm nylon 6,6 nonwoven fabrics. They showed that the tensile and compressive strength decreased with improved areal weight density by about 41% and 13%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…As previously stated, although the microfiber interleaving improves Mode-I fracture toughness significantly, it deteriorates in-plane mechanical properties of composite laminates due to the reduced fiber volume fraction, thickness increase and formation of voids. 25 In nanofiber interleaving technique, it is possible to improve not only delamination resistance but also in-plane mechanical properties of composite laminates. This win-win situation is the unique characteristic of nanofiber interleaving technique.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[18] The above methods are effective on fiber-reinforced polymer composites, but complicated in fabrication, high in cost, and even cause loss of in-plane mechanical properties. [19,20] An approach that is excellent to alleviate the above challenges is matrix modification by adding particles. [21] Matrix modification by adding a proper amount of nano or micro particles can significantly improve the overall properties of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…10 A thermoplastic interleaved method which is inserted with a veil, nanofiber, nano-web, or microparticles at the interlaminer region have been adopted to interrupt crack propagation in fiber reinforced composites. [11][12][13][14][15] Liu et al 16 performed compression after impact (CAI) and transverse flexural experiments on Polyamide (PA)/ carbon epoxy and PA/Polyethersulfone (PES)/carbon epoxy composite laminates. The enhanced interlaminar properties were attributed to the toughening interlayer of the PA microparticles and strong interfacial adhesion between the PA microparticles and epoxy matrix.…”
Section: Introductionmentioning
confidence: 99%